Pengembangan Buku Panduan Pemetaan Tren dan Topik Penelitian Berbasis Aplikasi Vosviewer - Awaliyah, Mia; Amanah, Amanah; Cahyani, Putri Ayu (Indo-MathEdu Intellectuals Journal, 2024)
Identification of research trends and topics is a crucial aspect of academics and research to ensure the relevance, contribution, and novelty of a study. However, difficulties in identifying relevant and latest research trends and topics remain a significant challenge for researchers. The aim of this study is to produce a product in the form of a guidebook for mapping research trends and topics using the Vosviewer application. This research employs the Four-D model development design, consisting of four stages, of which definition, design, development, and dissemination. The data for this study were obtained through questionnaires distributed to media experts, content experts, and guidebook users. The data collection instrument was a questionnaire sheet. Data analysis was conducted using descriptive quantitative techniques to determine scores from validators and product users. The study produced a guidebook for mapping research trends and topics that excels in terms of content and design quality. From the content perspective, the guidebook received an average percentage of 45.3% categorized as "very appropriate" and 54.6% categorized as "appropriate." From the design perspective, the guidebook received an average score percentage of 64.5% categorized as "very appropriate" and 48% categorized as "appropriate." This guidebook can be utilized to build academic identity, demonstrate research originality, and address contemporary needs